Eukaryotic Initiation Factor 4A-3: A Review of Its Physiological Role and Involvement in Oncogenesis - Ye, Jiazhou; She, Xiaomin; Liu, Ziyu; He, Ziqin; Gao, Xing; Lu, Lu; Liang, Rong; Lin, Yan (Frontiers in Oncology, 2021)
EIF4A3, a member of the DEAD-box family, is a nuclear matrix protein and a core component of the exon junction complex (EJC). Under physiological conditions, EIF4A3 is involved in post-transcriptional gene regulation by promoting EJC control of precursor mRNA splicing, and it influences nonsense-mediated mRNA decay (NMD). In addition, EIF4A3 modulates the synthesis of selenoproteins to maintain the expression of significant ones, including phospholipid hydroperoxide glutathione peroxidase (PHGPx) and thioredoxin reductase 1 (TR1). Recently, several studies have found that EIF4A3 plays a tumor-promoting role in multiple human cancers, such as glioblastoma, hepatocellular carcinoma, pancreatic cancer, and ovarian cancer. Molecular biology studies show that EIF4A3 is recruited by long non-coding RNAs to regulate targeted protein expression in tumors. However, its tumor-related functions and underlying mechanisms are not well understood. Here, we review the physiological role of EIF4A3 and the evidence of an association between EIF4A3 over-expression and tumorigenesis. We also evaluate the protein’s potential utility as a diagnosis biomarker, therapeutic target, and prognosis indicator, hoping to provide new ideas for future research.